(untitled) (Costa Rican Journal of Guidance & Counseling, 2021)
This essay presents the main postulates of the Career Construction Theory and the Life Design Paradigm proposed by Mark L. Savickas. In addition, several of the criticisms that this approach receives are commented. For example, it responds to a contextual reality different from the one in Latin America. It also has a human capital logic that encourages individualization and that can be used only in individual counseling. Subsequently, a way to apply the main postulates of the Life Design Paradigm to the vocational guidance of groups in Latin American contexts is proposed. To achieve this, the narrative presented by this paradigm can be complemented by the critical and emancipatory approach of Paulo Freire’s critical pedagogy. In this way, the individualistic perspective that characterizes the postmodern world can be countered through a discourse of solidarity and social transformation. In addition, promoting cultural experiences that expand the worldview of students helps to configure positive vocational narratives that can favor the experience of vocations that seek to go beyond the realities of social injustice that characterize Latin American societies. To do this, a broad career vision is considered, one that includes not only educational trajectories and work occupations, but also volunteering, social, and family commitments that the person performs throughout their life.